Rearrangement of meta-Bridged Calix[4]arenes Promoted by Internal Strain - Slavík, Petr; Krupička, Martin; Eigner, Václav; Vrzal, Lukáš; Dvořáková, Hana; Lhoták, Pavel (The Journal of organic chemistry, 2019)
The meta-bridged calixarenes possess a rigidified and highly distorted cavity, where the additional single-bond bridge imposes an extreme internal strain on the whole system. As a consequence, these compounds exhibit a reasonably amended reactivity, compared with common calix[4]arene derivatives, which is governed by the release of internal strain. This can be documented by the reaction of the bridged calix[4]arene with P2O5 or Nafion-H, leading (apart from polymers) to a macrocyclic product with a rearranged basic skeleton. The methylene bridge next to the fluorene moiety is intramolecularly shifted from position 2 to position 4 of the phenolic subunit to minimize the tension. As revealed by single-crystal X-ray analysis and by application of the residual dipolar coupling method, the rearrangement occurs without altering the original conformation.